Improving the Quality of Graduates in Maintaining the Existence of Islamic Boarding Schools - Zahrotul Luqmi, Fitra; Patimah, Siti (Riviera Publishing, 2023)
The purpose of this study is to describe planning, organizing, achieving and evaluating based on improving the quality of the quality of student graduates in maintaining the existence of pesantren that have been implemented at Madrasah Aliyah Wali Songo Putri under the auspices of Pondok Pesantren